2015
DOI: 10.1021/ma5023742
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide/Epoxide Copolymerization via a Nanosized Zinc–Cobalt(III) Double Metal Cyanide Complex: Substituent Effects of Epoxides on Polycarbonate Selectivity, Regioselectivity and Glass Transition Temperatures

Abstract: In this study, we describe the substituent effect of epoxides on CO 2 / epoxide copolymerization catalyzed by a nanosized zinc−cobalt(III) double metal cyanide complex [Zn−Co(III) DMCC]. The Zn−Co(III) DMCC catalyzed the copolymerization of CO 2 with 11 epoxides with alkyl or aryl groups at 50−60°C within 15 h. The reaction afforded various CO 2 /epoxide copolymers with high epoxide conversion efficiencies up to 100%. The alternating degree (F CO 2 ) of the resulting copolymer was solely decided by the steric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 51 publications
2
47
1
Order By: Relevance
“…Stereopure (atactic, isotactic, and syndio-enriched) PPC is a ductile thermoplastic that has been studied for some time. [136][137][138][139][140][141] However, thermal and mechanical data on the stereopure materials is noticeably lacking, except for one study that examined the effects of regioregularity in PPC and derivatives. 136 To date, one of the most interesting epoxide-based polymers is enantiopure poly(propylene succinate).…”
Section: Degradable Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereopure (atactic, isotactic, and syndio-enriched) PPC is a ductile thermoplastic that has been studied for some time. [136][137][138][139][140][141] However, thermal and mechanical data on the stereopure materials is noticeably lacking, except for one study that examined the effects of regioregularity in PPC and derivatives. 136 To date, one of the most interesting epoxide-based polymers is enantiopure poly(propylene succinate).…”
Section: Degradable Polymersmentioning
confidence: 99%
“…[136][137][138][139][140][141] However, thermal and mechanical data on the stereopure materials is noticeably lacking, except for one study that examined the effects of regioregularity in PPC and derivatives. 136 To date, one of the most interesting epoxide-based polymers is enantiopure poly(propylene succinate). 142 By mixing the two enantiopure isotactic polymers that display slow crystallisation kinetics, a stereocomplex was formed with a dramatic improvement in crystallisation rate and T m .…”
Section: Degradable Polymersmentioning
confidence: 99%
“…However, Zhang and co‐workers showed that also aliphatic polycarbonates with a flexible backbone may exhibit T g s up to 84 °C depending on their side chains. While the T g decreases with increasing alkyl length to −38 °C, the glass transition may increase up to 84 °C by steric influences . Also long alkyl side chains with up to 20 carbon atoms were already incorporated in aliphatic polycarbonates to tune the thermal properties .…”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%
“…The immortal polymerization of PO in the presence of alcohols is a prominent feature of industrially applied double metal cyanide (DMCs) complexes for the preparation of narrow distributed polypropylene glycols [62]. The DMC catalysts for propoxylation may also yield poly(ether carbonates) when CO 2 is admitted, usually giving products with large contents of ether blocks (f carb << 75 mol%) [63][64][65] and with a lower activity [66]. The immortal copolymerization of CO 2 and epoxides can also be mediated by zinc carboxylate and DMC catalysts, giving a product with the signature of both catalysts [67].…”
Section: Introductionmentioning
confidence: 99%